2019
DOI: 10.1016/j.jcmgh.2019.03.001
|View full text |Cite
|
Sign up to set email alerts
|

Senescent Hepatocytes in Decompensated Liver Show Reduced UPRMT and Its Key Player, CLPP, Attenuates Senescence In Vitro

Abstract: Background and Aims Non-dividing hepatocytes in end-stage liver disease indicates permanent growth arrest similar to senescence. Identifying senescence in vivo is often challenging and mechanisms inhibiting senescence are poorly understood. In lower organisms mitochondrial unfolded protein response (UPR MT ) helps in increasing longevity; however, its role in senescence and liver disease is poorly understood. Aim of this study was to identify h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 43 publications
1
27
0
Order By: Relevance
“…Chronic liver injury reduced the proliferative response of hepatocytes due to a predominant STAT1 activation, whereas control animals showed an IL6-STAT3-mediated proliferative effect. That is not entirely surprising as the aforementioned human studies, 5,6 as well as pre-clinical studies focussing on the effect of TGFb1, have already proposed that cirrhosis negatively modulates liver tissues' regenerative capacities. 17 Importantly, the acute hepatotoxic injury with CCl 4 , despite limiting regeneration and inducing a severe liver injury, did not impair survival or long-term recovery.…”
Section: The New Link Between Disease Phenotype and Regenerative Mechmentioning
confidence: 91%
See 1 more Smart Citation
“…Chronic liver injury reduced the proliferative response of hepatocytes due to a predominant STAT1 activation, whereas control animals showed an IL6-STAT3-mediated proliferative effect. That is not entirely surprising as the aforementioned human studies, 5,6 as well as pre-clinical studies focussing on the effect of TGFb1, have already proposed that cirrhosis negatively modulates liver tissues' regenerative capacities. 17 Importantly, the acute hepatotoxic injury with CCl 4 , despite limiting regeneration and inducing a severe liver injury, did not impair survival or long-term recovery.…”
Section: The New Link Between Disease Phenotype and Regenerative Mechmentioning
confidence: 91%
“…4 However, profound scientific evidence validating this hypothesis as well as an exploration of the underlying molecular mechanisms were lacking. Two recent studies in patients with acutely decompensated liver cirrhosis 5 and ACLF 6 showed that hepatocyte proliferation (Ki67), which is the major regenerative response after mild to moderate injury, was abrogated in end-stage liver disease. 6 However, these descriptive studies could not provide information about influencing factors or mechanisms.…”
mentioning
confidence: 99%
“…We speculate whether the YME1L1 transcription mRNA encoded by the nuclear genome is somehow increased by PGC-1α and is transported to the mitochondria for extensive expression, which remains to be further confirmed. The mitochondrial matrix protease Clp family consists of ClpAP, ClpCP, ClpEP, ClpXP and ClpYQ, which exist in the mitochondria of various prokaryotes and eukaryotes, as well as in the chloroplasts of algae and plant cells 49 . The active two-chain proteases are complex compounds consisting of a peptidase subunit (CLPP or ClpQ).…”
Section: Discussionmentioning
confidence: 99%
“…Due to these reasons, hepatocyte proliferation rates drop significantly during the stage of liver cirrhosis due to pathological adaption to stress. 104,105 Infected hepatocytes can manage the stress response through the induction of ISR that promotes the transcription of numerous genes for cell survival. 106 The significant reduction of hepatocyte proliferation in liver cirrhosis could activate stem cell compartment through epigenetic programming.…”
Section: Hepatocytes In the Liver Undergo Pathological Adaptation To mentioning
confidence: 99%